2020
DOI: 10.1177/1555412020975637
|View full text |Cite
|
Sign up to set email alerts
|

Are Video Games Still a Boys’ Club? How German Public Television Covers Video Games

Abstract: Games shape our understanding of culture. As market figures demonstrate, video games as digital successors of traditional games are now the economic drivers of the media and entertainment industry and form a part of our daily media habits. Since the mid-1970s, journalistic coverage has presented video games as a controversial issue, an image that has crucially shaped public opinion to this day. In the case of Germany, the Interstate Broadcasting Treaty (Rundfunkstaatsvertrag) demands that public broadcast serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
0
2
0
1
Order By: Relevance
“…Paralelamente a la consolidación de la industria se ha desarrollado el periodismo de videojuegos, que cada vez recibe más atención por parte de la academia (Bigl y Schlegelmilch, 2021;Braithwaite, 2016;Estanyol et al, 2018;López-Redondo, 2021;Paredes-Otero, 2021;Patridge, 2018). El papel de los medios, y en particular de la información especializada, no es menor en este sentido: el periodismo cultural destaca sobre el resto de áreas por su función prescriptiva, mediante la cual los profesionales, basándose en su criterio experto, deciden cuáles son los productos que merecen recibir la atención del público.…”
Section: Introductionunclassified
“…Paralelamente a la consolidación de la industria se ha desarrollado el periodismo de videojuegos, que cada vez recibe más atención por parte de la academia (Bigl y Schlegelmilch, 2021;Braithwaite, 2016;Estanyol et al, 2018;López-Redondo, 2021;Paredes-Otero, 2021;Patridge, 2018). El papel de los medios, y en particular de la información especializada, no es menor en este sentido: el periodismo cultural destaca sobre el resto de áreas por su función prescriptiva, mediante la cual los profesionales, basándose en su criterio experto, deciden cuáles son los productos que merecen recibir la atención del público.…”
Section: Introductionunclassified
“…Other research tropes can be suggested here by studies indicating how news media in various countries evaluate games in general (not only esports). For example, there are some reports on growing game acceptance in the US (Williams, 2003) or Germany (Bigl & Schlegelmilch, 2021), while in China the status of gaming is still rather doubtful (Cao & He, 2021). Overall, we believe that our qualitative inquiry could be a starting point for further analysis, including cross-cultural ones, as these have just begun in esports research in general (e.g.…”
Section: Discussionmentioning
confidence: 89%
“…Back in 2016, the video game market in the USA was valued at over $17 billion mainly through three companies, namely Microsoft, Sony and Nintendo, monopolizing the home video game industry [21]. In Germany, the gaming industry is ahead of other cultural and media industries with more than 6.2 billion euros in revenue a number to grow 19% in 2023 [22]. The popularity of video games in the past decade is also empowered by the rapid development of smart mobile devices [8].…”
Section: Power Of Gamesmentioning
confidence: 99%